Effect of oleic acid content and chemical crosslinking on the properties of palm oil‐based polyurethane coatings. Issue 1 (16th November 2012) - Velayutham, T. S.; Abd Majid, W. H.; Ng, B. K.; Gan, S. N.
Abstract Polyurethanes (PU) were prepared by reacting palm oil‐based polyols and aromatic diisocyanate (toluene 2, 4 diisocyanates). The content of oleic acid was varied in the polyester polyols and the hydroxyl value was fixed to be 140 mg KOH g−1. The NCO/OH ratios were varied to 1.2, 1.4, and 1.6. Crosslinking density of the PU was measured by swelling in toluene at room temperature. It was found that the crosslinking increased with decreasing oleic acid content and increasing NCO/OH ratio. The samples were assessed by thermogravimetric analysis, differential scanning calorimetric, and short‐term creep measurements. The highest rupture strength of the PU films was 36 MPa and thermostability improved as the oleic acid content and the NCO/OH ratios were increased in the sample. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013